Well-Preserved Boundaries: Faith and Co-Existence in the Late Ottoman Empire - Göktürk, Gülen (Birmingham Byzantine and Ottoman Studies, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures -- Acknowledgments -- Introduction -- 1. Ottoman tolerance reconsidered -- 2. Maintaining boundaries: Faith and co-existence in late Ottoman Cappadocia -- 3. The path toward nationalism -- 4. Halasane ta pragmata (Things spoiled) -- 5. Tolerating the heretics -- Conclusion -- Bibliography -- Index.